Proving the Feasibility of D-Band Single SiGe MMIC Vector Network Analyzer Extension Modules With Large System Dynamic Range - Justin Romstadt; Lukas Dierkes; Stephan Hauptmeier; Tobias T. Braun; Hakan Papurcu; Jens Richter; Pascal Stadler; Ahmad Zaben; Klaus Aufinger; Jan Barowski; Nils Pohl (IEEE Journal of Microwaves)
The need for size and cost-efficient vector network analyzer (VNA) frequency extension modules (VNAX module) is driven by new applications in research and industry. Responding to this potential demand, we present a novel D-band VNAX module based on a single SiGe MMIC. Our work addresses the challenges associated with integrating components on a single chip compared to conventional commercial modules, which typically rely on discrete components. We provide a comprehensive discussion covering the performance of system blocks, such as multiplier chains and receivers, and their impact on the module's performance. In addition, we present extensive measurements of the entire system, including magnitude-and phase stability and dynamic ranges. At a resolution bandwidth (RBW) of 10 Hz, our module shows a system dynamic range (SDR) above 90 dB for the frequency range of 110 GHz to 151 GHz and a maximum SDR close to 100 dB at 122 GHz. The corresponding receiver dynamic range within the D-band ranges from 113 dB to 125 dB, and the Test Port power is between −27 dBm and −16 dBm. In addition, we present and evaluate several measurements of different passive components that verify the calibration capability of our module.